2011
DOI: 10.21273/hortsci.46.4.553
|View full text |Cite
|
Sign up to set email alerts
|

Historical Trends in Strawberry Fruit Quality Revealed by a Trial of University of Florida Cultivars and Advanced Selections

Abstract: The University of Florida strawberry (Fragaria ×ananassa Duch. ex Rosier) breeding program has maintained a continuous breeding effort since 1968 to develop cultivars that are highly adapted to winter production in west-central Florida. To gain insight into breeding progress over time, two advanced selections (UF1 and UF2) and 10 released cultivars, from Florida Belle (1975) to Florida Radiance (2008), were compared for various fruit quality traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 19 publications
4
49
1
2
Order By: Relevance
“…Fruit are cultivated according to current commercial practices for annual strawberry plasticulture in Florida [1], [29](Fig. 1A).…”
Section: Methodsmentioning
confidence: 99%
“…Fruit are cultivated according to current commercial practices for annual strawberry plasticulture in Florida [1], [29](Fig. 1A).…”
Section: Methodsmentioning
confidence: 99%
“…Improvements in quality traits such as fruit size, yield uniformity, and cull rates have been evident when comparing cultivars from different eras (Whitaker et al 2011). However, regular screening for PhCR has been conducted at UF only in the last 5 yr.…”
mentioning
confidence: 99%
“…It may also be advisable to evaluate color of advanced selections both before and after cold storage. An analysis of released UF strawberry cultivars indicated that those noted for their attractive, bright red external coloration had the highest a* values and often had the highest L* values (Whitaker et al 2011). Those that were often regarded as having a dark, overripe appearance had the lowest L* values.…”
Section: Discussionmentioning
confidence: 99%